Analisis dan Perancangan Jaringan Wireless Dengan Wireless Distribution System Menggunakan User Authentication Berbasis Multi-Factor Authentication - Muchamad Rusdan; Muhamad Sabar (LPPM STMIK AMIK BANDUNG, 2020)
Wireless networks are one of the best alternatives in building practical and flexible computer networks that have high mobility. Most of them use wireless networks to support existing cable networks, but on wireless networks, they still use cable media as a backbone of the access point, which supports communication users can access the internet and find information. The problem of using cables as backbone media can be a significant challenge in places that are difficult to reach by wires. Wireless networks provide convenience and convenience that is high enough to use. As long as they are in an area that is supported by a wireless network, users can access the internet at any time. To make the wireless network connected to the internet safe and easy to use, we can create a user authentication system based on Multi-Factor Authentication (MFA) that can be used to authenticate and authorize. In general, each user can use existing wireless network services by verifying users based on Wifi Protected Access 2 Pre-Shared Key (WPA2-PSK). The purpose of this research is to develop a wireless network that uses Multi-Factor Authentication (MFA) based user authentication to be able to connect to the wireless network to increase security and provide the use of existing wireless networks. The research method used in this study uses descriptive qualitative research methods, with data collection using literature study and observation techniques. After analysis and design, it can be concluded that user authentication is based on Multi-factor Authentication (MFA) in a safe and user-friendly manner that can determine the users who are allowed and not allowed to use wireless networks.